ProPelled: The Effects of Grants on Graduation, Earnings, and Welfare - Jeffrey T. Denning; Benjamin M. Marx; Lesley Turner (Institute of Labor Economics (IZA), 2018)
We estimate effects of the Pell Grant - the largest U.S. federal grant for college students - using administrative data from Texas public colleges and a discontinuity in grant generosity for low-income students. Within four-year institutions, eligibility for additional grant aid significantly increases first-time students' degree completion and later earnings. Our estimated impacts on earnings alone are enough to fully recoup government expenditures within 10 years, suggesting that financial aid likely pays for itself several times over.
Keywords: H52; I22; I26; 330; Pell Grant